SEMANTIK PROTOTIPE KORUPSI: KAJIAN LINGUISTIK KOGNITIF - Millatuz Zakiyah; Noveria Anggraeni Fiaji; Prima Zulvarina (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
Semantics Corruption Prototype: Cognitive Linguistic Study. Semantic Prototype Corruption: Cognitive Linguistics Review. This study aims to define corruption through prototype theory in cognitive linguistics. The research is designed through a qualitative-quantitative approach with Tomaszczyk (2007) prototype theory. The results of the study indicate that the most corrupt variables affecting the degree of corruption are (1) 'unlawful rewards' and (2) 'abuse of authority', while (3) 'knowing that it is corruption' and (4) 'corrupt intent' no effect. Based on the background of respondents there is no difference in the degree of degree of corruption.